Integration of ESG (Environmental, Social, Governance) Criteria in Islamic Finance: A Systematic Review - Jery Wardiman,; M Topit Hidayat,; Zul Afdal,; Nofriansyah, (LAA MAISYIR : Jurnal Ekonomi Islam, 2024)
The integration of Environmental, Social, and Governance (ESG) factors in Islamic finance is methodically examined in this paper, with a focus on how Sharia rules connect with sustainability objectives. Examining the benefits and difficulties of implementing ESG principles in Islamic financial institutions is the primary goal. This study identifies important findings from recent research and examines their implications for Islamic finance using a systematic literature review (SLR) based on the PRISMA approach. According to the analysis, there are still a lot of obstacles to overcome, especially when it comes to standardized reporting and regulatory guidelines, even though ESG closely resembles Maqasid al-sharia in that it promotes social welfare and ethical governance. The findings demonstrate how increasing ESG practice transparency can boost market competitiveness, draw in socially conscious investors, and advance the Sustainable Development Goals (SDGs). The results of this study provide a conceptual framework for Islamic financial institutions looking to implement Sharia-compliant ESG practices, laying the groundwork for future empirical studies and policy creation.